Itinerarios y experimentación en el arte de los años 80. Una cartografía desbordada de espacios del “underground” en Buenos Aires - Marina Suarez (Centre de Recherches sur les Mondes Américains, 2019)
Towards the end of the dictatorship and the beginning of democracy, Buenos Aires witnessed the formation of an artistic movement cataloged by the public and the press as "underground". Their intense and ephemeral actions were developed mainly in precariously sustained production spaces, often transitory and also on public roads ". However, they also soon joined official institutions linked to "high culture" or public dependency. The city that during the years of military dictatorship (1976-1983) had remained strictly, controlled, watched, limited, became, with the return of democracy, an extension for experimentation, configuring new ways of inhabiting it. It was so that the artists did not delay in reproducing it. The objective of the present work is to reconstruct a cartography of counterculture spaces (in opposition to those of the hegemonic culture) postulating that artists traveled, not only by improvised and precarious sites, but also by official and public institutions.